2021
DOI: 10.1016/j.jaci.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mastocytosis and Hymenoptera venom allergy in the United States

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although a recent study showed a lower prevalence of MCD among the U.S. population compared to Europe, that study was highly susceptible to reporting bias [81]. The incidence of side effects during VIT in mastocytosis patients has been noted in up to 18.9% [82].…”
Section: Adverse Side Effects and Risk Factorsmentioning
confidence: 94%
“…Although a recent study showed a lower prevalence of MCD among the U.S. population compared to Europe, that study was highly susceptible to reporting bias [81]. The incidence of side effects during VIT in mastocytosis patients has been noted in up to 18.9% [82].…”
Section: Adverse Side Effects and Risk Factorsmentioning
confidence: 94%
“…23 The reported prevalence of SM in the general population ranges from 10 to 17.2 per 100.000 inhabitants and is far higher among patients with HVA, with reported rates varying between reports and by geographic area (1.8% in the US, 3.8% in Israel, and 1-7.9% in European cohorts). [24][25][26][27][28] According to the 2016 WHO classification, a diagnosis of SM is made if one major and one minor or three minor criteria are met; however, discoveries over the past few years have resulted in a push towards an updated set of diagnostic criteria (see Table 1). 23,29 In addition to the established disease subsets mentioned above, two distinct entities of interest have recently been identified; namely, monoclonal mast cell activation syndrome (MMAS) and bone marrow mastocytosis (BMM).…”
Section: Key Messagesmentioning
confidence: 99%
“…Nine out of 161 (5.6%) patients undergoing venom immunotherapy (VIT) had basal tryptase >11.4 ng/mL, and 3 (1.8%) had a clonal mast cell disorder. 24 …”
Section: Hymenoptera Venom Allergy and Mast Cell Activation Syndromesmentioning
confidence: 99%